(3cTa GdZWGAs - (3GdMdj, GdLfGLj, GdfLaj, ef Bd cGTa GdZWGA, LYaQ Hf NVQ Hf TdGd, J (B1227 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPj ZeQ GdNdGFb HGdfYe, hTed GdcGFfGJ HGddWa GdLejd(B...(3CeG HYO aEfj HYO eG UfaJ QSGdI eNJUQI dHjGf CMcGe GdTQjYI GdWGgQI GdeWgQI(B...(3Cf CcJH QSGdI eHShWI hGajIhaj HjGf aQhY GdCMcGe cGajI TGajI(B...s
(3BNQgG (B:s
...(3hYf GdUGOb Y Cf EHQGgje Y Ndjd GdQMef SCd Gddg (B- (3SHMGfg (B- (3GHfI JHcjg HYO ehJg Edi ZjQ Pdc ef GdCNHGQ hGddg hdj GdJhajbs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B2(3,U(B124s
(3eYLe GdeDdajf(B:(3L(B1(3,U(B491s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis